Itraconazole Promotes Macrophage M1 Polarization and Phagocytic Capacity of Macrophage to Candida Albicans - Xiao-Li Zheng; Guan-Zhao Liang; Dong-Mei Shi; Hui-Ping Yao; Lu Zhang; Wei-Da Liu; Guan-Zhi Chen (International Journal of Dermatology and Venerology, 2019)
Abstract. Objective:. The present study was designed to evaluate whether and how itraconazole affects the macrophage polarization and its reactivity to Candida albicans. Methods:. Cell toxicity of itraconazole was measured using cell counting kit-8 assay in RAW264.7 cells. The cell models were induced by lipopolysaccharide (LPS), interleukin (IL)-4, or Candida albicans. Levels of cytokines secreted by RAW246.7 treated with itraconazole were detected by Luminex or Cytometric Bead Array compared to the controls without itraconazole treatment, and the expressions of inducible nitric oxide synthase and arginase (Arg) were determined by Western blot. Phagocytosis ability was measured by both flow cytometry and fluorescence microscope. The Student's t test and one-way analysis of variance were used to calculate the differences between groups. Results:. In comparison to the control, itraconazole inhibited the growth of the cells in both a time- and a dose-dependent manner. Increased secretion of IL-6 (0.25 μmol/L ITZ [538.03 ± 60.23 pg/mL, P < 0.05], 0.5 μmol/L [550.32 ± 47.87 pg/mL, P < 0.05] and 1 μmol/L [626.95 ± 75.24 pg/mL, P < 0.01] vs. control [370.43 ± 33.98 pg/mL]) and tumor necrosis factor-alpha (TNF-α) (1 μmol/L ITZ vs. control: 2521.51 ± 444.06 pg/mL vs. 1617.85 ± 94.57 pg/mL, P < 0.05) were detected in the LPS-induced cell model with itraconazole treatment. In the cells induced by IL-4, itraconazole increased the secretion of IL-6 (1 μmol/L ITZ vs. control: 528.33 ± 11.60 pg/mL vs. 466.99 ± 28.32 pg/mL, P < 0.05), TNF-α (1 μmol/L ITZ vs. control: 4.85 ± 0.32 pg/mL vs. 4.30 ± 0.19 pg/mL, P < 0.05), and IL-1β (0.25 μmol/L [325.95 ± 13.97 pg/mL, P < 0.05], 0.5 μmol/L [332.38 ± 11.97 pg/mL, P < 0.05] and 1 μmol/L [334.35 ± 16.23 pg/mL, P < 0.05] vs. control [291.62 ± 17.03 pg/mL]), and reduced the secretion of IL-10 (1 μmol/L ITZ vs. control: 7.21 ± 0.68 pg/mL vs. 9.11 ± 0.14 pg/mL, P < 0.05). The secretion of IL-6 (1 μmol/L ITZ vs. control: 38.34 ± 1.36 pg/mL vs. 32.32 ± 0.84 pg/mL, P < 0.05) and TNF-α (1 μmol/L ITZ vs. control: 1060.17 ± 80.16 pg/mL vs. 890.84 ± 52.82 pg/mL, P < 0.01) was improved in Candida albicans-stimulated RAW264.7 cells under the treatment of itraconazole, while the secretion of IL-4 (0.5 μmol/L [2.86 ± 0.20 pg/mL, P < 0.05] and 1 μmol/L [2.24 ± 0.33 pg/mL, P < 0.001] vs. control [3.91 ± 0.23 pg/mL]) and IL-10 (1 μmol/L ITZ vs. control: 19.46 ± 2.05 pg/mL vs. 25.67 ± 1.95pg/mL, P < 0.05) decreased. In all three activated patterns, itraconazole enhanced the expression of inducible nitric oxide synthase (P < 0.01) and slightly inhibited the Arg-1 expression (P < 0.05). Phagocytosis ability of RAW264.7 cells at 1 μmol/L ITZ treatment was increased by 7.53% ± 2.21% (P < 0.01) and 9.73% ± 2.03% (P < 0.01) at the ratio of cells: yeast of 1:4 and 1:8, respectively, in comparison to the control group. Conclusion:. Itraconazole improved M1 polarization of RAW264.7 cells and enhanced the phagocytic capacity of RAW264.7 to Candida albicans, indicating a significant immunological enhancement. The study improves the understanding of undergoing mechanisms related to the anti-tumor and anti-infection effects of itraconazole.